Philosophy Of Science As An Epistemological Foundation In The Development Of Islamic Education Management Theory - Yani, Ahmad (Institut Agama Islam Al-Aziziyah Samalanga, 2024)
Islamic education has a strong foundation in the philosophy of science, which acts as an epistemological foundation in the development of educational management theory. This study aims to analyze the relationship between philosophy of science and Islamic education management, as well as its implications for educational practice. Using a qualitative approach, this research examines various perspectives of philosophy of science, such as empiricism, rationalism and constructivism, and their relevance in the context of Islamic education. The results show that a deep understanding of the philosophy of science can enrich educational management theory, enabling the integration of Islamic values in the process of educational management. In addition, the findings indicate the need for curriculum development that reflects epistemological principles in accordance with Islamic teachings, in order to improve the effectiveness of educational management. Thus, philosophy of science not only serves as an analytical tool, but also as a guideline in formulating educational management policies and strategies based on Islamic values.